Investigating mixotrophic metabolism in the model diatom Phaeodactylum tricornutum. (17th July 2017) - Villanova, Valeria; Fortunato, Antonio Emidio; Singh, Dipali; Bo, Davide Dal; Conte, Melissa; Obata, Toshihiro; Jouhet, Juliette; Fernie, Alisdair R.; Marechal, Eric; Falciatore, Angela; Pagliardini, Julien; Le Monnier, Adeline; et al.
Abstract : Diatoms are prominent marine microalgae, interesting not only from an ecological point of view, but also for their possible use in biotechnology applications. They can be cultivated in phototrophic conditions, using sunlight as the sole energy source. Some diatoms, however, can also grow in a mixotrophic mode, wherein both light and external reduced carbon contribute to biomass accumulation. In this study, we investigated the consequences of mixotrophy on the growth and metabolism of the pennate diatom Phaeodactylum tricornutum, using glycerol as the source of reduced carbon. Transcriptomics, metabolomics, metabolic modelling and physiological data combine to indicate that glycerol affects the central-carbon, carbon-storage and lipid metabolism of the diatom. In particular, provision of glycerol mimics typical responses of nitrogen limitation on lipid metabolism at the level of triacylglycerol accumulation and fatty acid composition. The presence of glycerol, despite provoking features reminiscent of nutrient limitation, neither diminishes photosynthetic activity nor cell growth, revealing essential aspects of the metabolic flexibility of these microalgae and suggesting possible biotechnological applications of mixotrophy. This article is part of the themed issue 'The peculiar carbon metabolism in diatoms'.